2022
DOI: 10.1177/10556656221136177
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Analysis on Clinical Severity of Mandibulofacial Dysostosis Guion-Almeida Type

Abstract: Objective Genetic variants in EFTUD2 were proven to influence variable phenotypic expressivity in mandibulofacial dysostosis Guion-Almeida type (MFDGA) or mandibulofacial dysostosis with microcephaly (MFDM). Yet, the association between the severity of clinical findings with variants within the EFTUD2 gene has not been established. Thus, we aim to elucidate a possible genotype–phenotype correlation in MFDM. Methods Forty articles comprising 156 patients were evaluated. The genotype–phenotype correlation was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These include missense mutations, nonsense mutations, insertions, small deletions/duplications, splice site mutations and large gene deletions. The mutations are found in the exonic (67.7%) or intronic (31.6%) regions, with no mutation hotspot found within EFTUD2 (Ulhaq et al., 2024 ). Most of the mutations are predicted to result in haploinsufficiency of EFTUD2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include missense mutations, nonsense mutations, insertions, small deletions/duplications, splice site mutations and large gene deletions. The mutations are found in the exonic (67.7%) or intronic (31.6%) regions, with no mutation hotspot found within EFTUD2 (Ulhaq et al., 2024 ). Most of the mutations are predicted to result in haploinsufficiency of EFTUD2 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are only approximately 150 reported cases of MFDM that have been confirmed to carry EFTUD2 mutations and most of these are individuals of European descent. There are still limited numbers of patients with an Asian background (Ulhaq et al., 2024 ). The phenotypic and genotypic spectrum of MFDM needs to be expanded to fully understand the clinical characteristics and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…EFTUD2 is an essential component of the spliceosome complex, acting as a character that shears pre-mRNAs to produce mature mRNAs [12] . EFTUD2 has been implicated in several diseases, including Mandibulofacial Dysplasia [13] , Guion-Almeida Type (MFDGA) [14] , Alzheimer's disease [15] , and various cancers [16][17][18] . Signi cantly, recent studies have revealed a close correlation between EFTUD2 and digestive system diseases, particularly liver cancer, where it exhibits signi cant upregulation.…”
Section: Introductionmentioning
confidence: 99%